2019
DOI: 10.1016/j.csbj.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Catalytic Mechanisms of Veratryl Alcohol Oxidation by Lignin Peroxidase: A Theoretical and Experimental Study

Abstract: Lignin peroxidase (LiP) and its natural substrate veratryl alcohol (VA) play a crucial role in lignin degradation by white-rot fungi. Understanding the molecular determinants for the interaction of this enzyme with its substrates is essential in the rational design of engineered peroxidases for biotechnological application. Here, we combine computational and experimental approaches to analyze the interaction of Phanerochaete chrysosporium LiP (isoenzyme H8) with VA and its radical cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…In the case of AauDyPI, a surface tyrosine and tryptophan-based radical centre were reported [63]. Our result is in line with the previously reported LRET pathways in lignin peroxidase (LiP) and versatile peroxidases (VP) [66][67][68]. Using QM/MM approaches and mutagenesis experiments, the authors reported a possible LRET pathway from the substrate to the heme centre involving electron transfer via 3 aromatic amino acids [67].…”
Section: Oxidation Of An ß-Aryl Ether Lignin Model Substrate and Veratryl Alcoholsupporting
confidence: 90%
“…In the case of AauDyPI, a surface tyrosine and tryptophan-based radical centre were reported [63]. Our result is in line with the previously reported LRET pathways in lignin peroxidase (LiP) and versatile peroxidases (VP) [66][67][68]. Using QM/MM approaches and mutagenesis experiments, the authors reported a possible LRET pathway from the substrate to the heme centre involving electron transfer via 3 aromatic amino acids [67].…”
Section: Oxidation Of An ß-Aryl Ether Lignin Model Substrate and Veratryl Alcoholsupporting
confidence: 90%
“…Interestingly, St DyP exhibited Mn 2+ -oxidizing activity, which was thought to be the catalytic feature of manganese peroxidase and versatile peroxidase [ 27 , 28 ]. Moreover, St DyP was able to oxidize the non-phenolic substrate VA, which is the characteristic of high redox potential peroxidases such as lignin peroxidase and versatile peroxidase [ 29 , 30 ]. These results indicated that St DyP might have great potential for biodegradation due to its catalytic versatility.…”
Section: Resultsmentioning
confidence: 99%
“…In general, LiP has two calcium‐binding sites that maintain the enzyme's active center and are formed by four disulfide bonds responsible for maintaining the overall structure 33 . Romero et al 85 . described that the oxidation of LiP could happen in the heme cavity typical of peroxidases or when the Trp171 residue is on the enzyme's surface.…”
Section: Wrf and Their Lmesmentioning
confidence: 99%